The Effect of Sectorial Contributions to GDP on Environmental Degradation: A Verification of the Environmental Kuznets Curve Hypothesis in Nigeria - Falade, Olanipekun Emmanuel; Adeyemi, Williams Owolabi (Journal of Economics and Behavioral Studies, 2023)
This paper empirically verifies the validity of the Environmental Kuznets Curve (EKC) hypothesis in Nigeria by focusing on the relationship between key sectors of the Nigerian economy and environmental degradation. The study adopted the Autoregressive Distributed Lag (ARDL) model using time series data for the period 1981-2018. The bounds-testing approach proposed by Pesaran, Shin and Smith, (2001) was adopted to test for cointegration. The results show a long-run relationship between economic growth (disaggregated into key sectors) and environmental degradation measured by carbon dioxide emissions. In the short run, agriculture, industry and services sectors significantly explained the variation in carbon dioxide (CO2) emissions, while the construction sector does not have any significant effect on Carbon emissions both in the current and the future periods. Specifically, the industrial sector has a positive effect on CO2 emissions which confirms the short-run EKC hypothesis; while agriculture and services though were significant, have a negative effect on CO2 emissions, invalidating the short-run EKC hypothesis. In the long run, industry and services sectors were significant in explaining variation in CO2 emission. However, while the services sector shows a negative relationship with CO2 emission in line with the long-run EKC Hypothesis, the industrial sector invalidates the hypothesis with a positive effect. These results imply that the key sectors of the economy have varied effects on environmental degradation, hence the hypothesis is inconclusive. Nigeria is therefore advised to pursue economic growth via industrial and services sectors with an emphasis on environmental sustainability, which could be achieved through the use of renewable and cleaner technology in nation-building.